A Critical Appraisal of the Right of Inheritance of Children Born Out of Wedlock - Ajanwachuku, Michael Akpa (Hasanuddin Law Review, 2016)
The phenomenon of the so-called bastard children has growth astronomically worldwide. In Nigeria, the rights of children born out of wedlock to inherit their biological fathers who died intestate was wholly dependent on the acknowledgement of paternity. This paper attempts to unravel the recent development in the law of inheritance in Nigeria with respect to children born out of wedlock. It concludes from the review of case laws in Nigeria that there is a significant progressive development of the law in Nigeria. Absent acknowledgement of paternity, children born out of wedlock may now inherit their biological fathers if they can provide other evidence of paternity, including the use of DNA technology.